Antara Dasein dan Caritas Pemikiran Hannah Arendt mengenai Kekuasaan - Alex Seran (Respons: Jurnal Etika Sosial, 2009)
Abstract: The rediscovery of Arendt’s 1929 dissertation, Der Liebesbegriff bei Augustin, forces a modification of the standard of interpretation of Arendt’s relationship both to the Christian philosophic tradition and to Martin Heidegger. The dissertation is an extended encounter with Heidegger’s Dasein  through an inquiry of St Augustine’s thought of caritas. Arendt’s thought on Existenz was methodologically focused on a turn from death and committed to test Heidegger’s phenomenology of Being-towards-death. Although contingency is central to Arendt’s Existenz, she insisted on invalidating determinism at every opportunity which allowed her to transform the fact of birth into a miraculous exemplar of natality to begin her own “turn” away from Heidegger’s gridlock of givennes. For Arendt, birth regenerates the power of contingency of individual person inserted into a community, i.e., the existing web of conflicting wills and intentions. The study of Arendt’s dissertation is significant because all her later works can be read as footnotes to it, as Jean Elshtain termed it.Kata Kunci: Dasein, existenz, waktu, natalitas